Strategi Pemerintah Desa dalam Pencegahan Stunting di Desa Kedungkendo Kecamatan Candi Kabupaten Sidoarjo - Fury Fidianti Putri; Hendra Sukmana (Program Studi Administrasi Negara Universitas Serang Raya, 2022)
This study aims to determine the village government's strategy in preventing cases of stunting risk. This research method is descriptive qualitative. The type of data used in this study is qualitative data, which is divided into primary data and secondary data. The village government's strategy in preventing cases of stunting risk is the focus of this research. Sources of data obtained from interviews and observations. The results of this study indicate that the village government's strategy in preventing stunting has not been achieved, this is due to a lack of public awareness of stunting, and the community does not understand stunting. With the village government's strategy of carrying out stunting prevention activities by implementing the Healthy Living Community Movement through nutrition improvement training and acupressure massage